2016
DOI: 10.1021/acsami.6b09482
|View full text |Cite
|
Sign up to set email alerts
|

Interlaced, Nanostructured Interface with Graphene Buffer Layer Reduces Thermal Boundary Resistance in Nano/Microelectronic Systems

Abstract: Improving heat transfer in hybrid nano/microelectronic systems is a challenge, mainly due to the high thermal boundary resistance (TBR) across the interface. Herein, we focus on gallium nitride (GaN)/diamond interface-as a model system with various high power, high temperature, and optoelectronic applications-and perform extensive reverse nonequilibrium molecular dynamics simulations, decoding the interplay between the pillar length, size, shape, hierarchy, density, arrangement, system size, and the interfacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 78 publications
0
17
0
4
Order By: Relevance
“…Our approach is inspired by macro-scale fin arrays that are conventionally used to enhance heat transfer between solid surfaces and fluids by increasing contact area [29]. Previous research has explored the use of micro-structured surfaces for thermal interface materials at the chip packaging level [30,31], and computational studies have suggested that the extension of this idea to atomic length scales can be beneficial to interfacial conduction [32]. However, the demonstration of nanostructured interfaces between solids in intimate contact, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is inspired by macro-scale fin arrays that are conventionally used to enhance heat transfer between solid surfaces and fluids by increasing contact area [29]. Previous research has explored the use of micro-structured surfaces for thermal interface materials at the chip packaging level [30,31], and computational studies have suggested that the extension of this idea to atomic length scales can be beneficial to interfacial conduction [32]. However, the demonstration of nanostructured interfaces between solids in intimate contact, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[175][176][177][178] Along this line, some interfacial improvement on the phonon transport can be achieved by optimizing the interfacial nanostructure. [157,160,[179][180][181][182][183] On the other side, a deposited diamond film as a heat spreader on top of the device is also less useful when nanoscale columnar grains are found. [152] New growth conditions to maximize the crystallization must be addressed to reach the full potential of diamond for thermal transport.…”
Section: Thermal Measurements and Thermal Engineering Of Gbsmentioning
confidence: 99%
“…It is known that physical properties such as mechanical, thermal, and electrical properties of 2D materials (e.g., BN sheets) are affected by ripples. [35][36][37][38][39][40][41] For instance, in the case of mechanical properties, the ripples provide high toughness (due to extra stretch as a result of unfolding of the ripples) while the ultimate strength is not sacrificed; two properties that are conflicting (i.e., high toughness and high strength). [42][43][44][45][46][47][48][49][50] Thus, having these sheets slightly crumpled can increase their toughness to be more flexible (stretchable) to internal pressure or external loads, thereby increasing their safety due to impact, damage, etc, which is one of the major concerns for safe H 2 storage and transport.…”
Section: Hydrogen Storagementioning
confidence: 99%
“…While BN sheets are typically flat, the synthesis conditions (impurities, asymmetric junctions, etc) may lead to wavy sheets that may have ripples, such as the 3D BN studied here. It is known that physical properties such as mechanical, thermal, and electrical properties of 2D materials (e.g., BN sheets) are affected by ripples . For instance, in the case of mechanical properties, the ripples provide high toughness (due to extra stretch as a result of unfolding of the ripples) while the ultimate strength is not sacrificed; two properties that are conflicting (i.e., high toughness and high strength) .…”
mentioning
confidence: 99%